Implementation of Outing Class Learning and Impact on Students in MTs Mamba’ul Ma’arif - Kharisma, Devi Khavita (JELP Journal of English Language and Pedagogy, 2024)
Education plays an important role in a person's life and development because basically education a is knowledge that can help humans to live life and keep up with the times. One way to provide creative and innovative education is through the outing class. Outing class is a popular method for implementing student-centred learning by taking them out of the traditional classroom environment. This paper aims to examine the application of outing classes in learning at MTs Mamba'ul Ma'arif. It also shows the impact on outing class’s student learning there. It uses a qualitative descriptive approach involving MTs Mamba’ul Ma’arif teachers and students. The data was collected through observation, interviews and documentation. The result is the implementation of outing class in MTs. Mamba'ul Ma'arif contributes significantly to student learning. Outdoor classes offer the students opportunity to learn outside and experience hands-on real-world learning. In addition, it also increases their learning motivation and involvement. However, the challenge in implementing outing class is also not easy because there will be several obstacles, including limited time, costs, and preparation needed to organize outing class activities. Therefore, the support from the schools, teachers and parents is very important in ensuring the implementation of outing classes and maximizing their benefits